Positioning Analysis of Chicken Rocket Mapping at Fast Food Restaurant Manarap Branch Banjarmasin - S. Purnamasari; Kurniaty; Norfitriana; Zakiyah; Purnama Rozak (East Asian Journal of Multidisciplinary Research, 2022)
Along with the changing times, the tendency of people to eat outside the home is increasing for various practical, economic and prestige reasons. Rocket Chicken is one of the fast food restaurant companies that has recently grown and has opened branch outlets everywhere, especially in the city of Banjarmasin. The role of price in buyer's perception is on product quality, value sacrifice and desire to buy, while location or place often determines the company's success, because location is closely related to a company's potential market. The problems in this study are as follows: How is the positioning from the aspect of price and place in creating a competitive advantage? How to apply Rocket Chicken positioning in Islamic Economic Perspective?. The purpose of this study was to determine the positioning of Rocket Chicken from the aspect of price and place in creating a competitive advantage and to determine the application of Rocket Chicken's positioning in an Islamic Economic Perspective. The benefits of this research can be used as consideration for companies, as well as knowledge that can provide information for all people, in an effort to improve knowledge in the field of Islamic economics. Qualitative research method with the type of field research(field research). The results show that: 1) Rocket Chicken provides food and beverage packages at affordable prices, creating a comfortable atmosphere.2) And in accordance with Positioning in Islam, namely the name or identity of a good and quality brand, consumers buy the product not because of coercion.